# Prove that $\prod_{i=1}^n\left(\frac{1}{x_i^2}-1\right)\ge (n^2-1)^n$

Let $$n$$ be a positive integer and $$x_1,...,x_n$$ positive reals such that $$x_1+\dots+x_n=1$$. Prove that $$\prod_{i=1}^n\left(\frac{1}{x_i^2}-1\right)\ge (n^2-1)^n.$$

Now notice that if we apply Jensen's Inequality to $$f(x)=\ln\left(\frac{1}{x_i^2}-1\right)$$ We would get the exact inequality...except that $$f$$ is not convex on $$(0,1)$$. But I do know this,

Claim: If for all $$k\le n$$ we have $$0< a_k\le 1/2$$. Then, $$\prod_{i=1}^n\left(\frac{1}{a_i}-1\right)\ge \left(\frac{n}{a_1+...+a_n}-1\right)^n$$

The proof is not too hard. Just consider $$g(x)=\ln\left(\frac{1}{x}-1\right)$$

$$g$$ is convex on $$(0,1/2)$$ and you can finish with Jensen. Now what if we let $$a_i=x_i^2$$? Well, we would get $$\prod_{i=1}^n\left(\frac{1}{x_i^2}-1\right)\ge \left(\frac{n}{x_1^2+...+x_n^2}-1\right)^n\ge (n^2-1)^n$$

Because $$x_1+...+x_n=1$$ implies, $$\sum_{i=1}^n x_i^2\ge \frac{1}{n}\left(\sum_{i=1}^n x_i\right)^2=\frac{1}{n}$$ And we're done...Or are we? The argument is only valid if $$x_i^2\le 1/2$$ for all $$i$$. Well if there exists $$x_i^2>1/2$$ Can we still get the inequality?

By the way there is a way to solve the inequality without any use of Jensen. But I want to know if we can solve it like that.

• The argument is only valid of $x_i^2 \leq 1/2$ (which is more relaxed than $x_i < 1/2$). So, one way out is to consider what happens if $x_1 > 1/2$. Maybe the product of the other terms would be large enough to counter. Feb 15 at 23:03
• I think that from $\sum x_i^2\ge1/n$ you cannot conclude that $\frac{n}{\sum x_i^2}\ge n^2$ because in the second statement the $\sum x_i^2$ is in the denominator. Feb 15 at 23:17
• Solution on AoPS: artofproblemsolving.com/community/c6h1602777p9982388 Feb 16 at 4:17

WLOG, assume that $$x_1 \le x_2 \le \cdots \le x_n$$.

We split into two cases:

Case 1: $$x_n < \frac{1}{\sqrt 3}$$

Note that $$x \mapsto \ln(\frac{1}{x^2} - 1)$$ is convex on $$(0, \frac{1}{\sqrt 3})$$. We have $$\sum_{i=1}^n \ln\left(\frac{1}{x_i^2} - 1\right) \ge n\ln\left(\frac{1}{(\frac{x_1 + x_2 + \cdots + x_n}{n})^2} - 1\right) = n\ln(n^2 - 1).$$

Case 2: $$x_n \ge \frac{1}{\sqrt 3}$$

Let $$y_1 = x_1, y_2 = x_2, \cdots, y_{n-2} = x_{n-2}$$ and $$y_{n-1} = y_n = \frac{x_{n-1} + x_n}{2}$$. Then $$0 < y_i < \frac{1}{2}$$ for all $$i$$.

Note that $$x \mapsto \ln(\frac{1}{x^2} - 1)$$ is convex on $$(0, \frac{1}{\sqrt 3})$$. We have \begin{align*} \sum_{i=1}^n \ln\left(\frac{1}{y_i^2} - 1\right) \ge n\ln\left(\frac{1}{(\frac{y_1 + y_2 + \cdots + y_n}{n})^2} - 1\right) = n\ln(n^2 - 1) \end{align*} which results in $$\prod_{i=1}^{n-2}\left(\frac{1}{x_i^2}-1\right) \cdot \left(\frac{1}{(\frac{x_{n-1} + x_n}{2})^2} - 1\right)^2\ge (n^2-1)^n$$

It remains to prove that $$\left(\frac{1}{x_{n-1}^2}-1\right)\left(\frac{1}{x_n^2}-1\right) - \left(\frac{1}{(\frac{x_{n-1} + x_n}{2})^2} - 1\right)^2 \ge 0$$ which is true since \begin{align*} &\left(\frac{1}{a^2}-1\right)\left(\frac{1}{b^2}-1\right) - \left(\frac{1}{(\frac{a + b}{2})^2} - 1\right)^2 \\[6pt] ={}& \frac{a^2 + 6ab + b^2 - (a^2 + 4ab + b^2)(a + b)^2}{a^2b^2(a+b)^4}(a-b)^2\\ \ge{}& 0 \end{align*} where $$a = x_{n-1}, b = x_n$$ (using $$a + b < 1$$).

We are done.

• Nice, this inequality only can use AM-GM inequality to solve it Feb 16 at 1:03
• @math110 AM-GM solution is expected. Feb 16 at 1:16

Lemma:$$\left(\dfrac{1}{x}-x\right)\left(\dfrac{1}{y}-y\right)\ge 4^3\left(\dfrac{z^3}{3^9\cdot x^2y^2}\right)^{\frac{1}{4}}~~~~~(n=3)$$ $$LHS=\dfrac{1}{xy}\left(\dfrac{z}{3}+\dfrac{z}{3}+\dfrac{z}{3}+xy\right)\left(x+\dfrac{1}{3}+\dfrac{1}{3}+\dfrac{1}{3}\right)\left(y+\dfrac{1}{3}+\dfrac{1}{3}+\dfrac{1}{3}\right)\ge RHS$$ then $$\left(\dfrac{1}{x^2}-1\right)\left(\dfrac{1}{y^2}-1\right)\ge 4^3\left(\dfrac{z^3}{3^9\cdot x^2y^2}\right)^{\frac{1}{4}}\cdot\dfrac{1}{xy}$$

for any postive $$n$$ we have use AM-GM same methods $$\left(\dfrac{1}{x^2_{1}}-1\right)\left(\dfrac{1}{x^2_{2}}-1\right) \ge \left(n-\dfrac{1}{n}\right)^2\left(\dfrac{1}{n}\right)^{\dfrac{n^3-3n^2+2n-2}{(n-1)^2(n+1)}}\cdot(x_{1}x_{2}\cdots x_{n})^{\frac{n}{(n-1)^2}}\left(\dfrac{1}{x_{1}x_{2}}\right)^{\frac{n^2+1}{n^2-1}}\cdot\dfrac{1}{x_{1}x_{2}}$$